Relational Aspect Of Humanity In The Light Of (Selected) Athropological Asumptions Of The Theology Of The Body By John Paul II - Młynarski, Stanisław (Studia Theologica Varsaviensia, 2020)
The aim of the article is to present (selected) assumptions of anthropology that underlies the theology of the body of John Paul II. The author analyzes its main assumptions and confronts them with inadequate anthropology, which underlies the sexual revolution that is considered as distorting the sense of the human body in the light of Revelation. This study focuses on the analysis of the contents of the catechisms of John Paul II referring to texts about human relativity and the role that the body plays in this context. The analysis does not include those texts that refer to the reality of the sin of the first people. The text also aims at emphasizing the importance of the theology of the body for modern man and his spiritual development.